Concept and Different Types of Restrictive Business Practices in the Legal Orders of BRICS Countries (the Case of China, India, Russia and South Africa) - BELIKOVA, Ksenia Michailovna; BADAEVA, Natalia Vladimirovna; FROLOVA, Evgenia Evgenevna; DUDIN, Mihail Nikolaevich (Journal of Advanced Research in Law and Economics; Vol 8 No 2 (2017): Volume VII, Issue 2(24), Spring 2017, 2017)
The article represents a research of general approaches of BRICS countries legislation and legal order to counteraction against leading anticompetitive market strategies with regard to legal orders of China, India, Russia and South Africa. Different theoretical and practical approaches regarding establishment of legality or illegality of the agreements able to be considered as restrictive business practice under the law of China, India and South Africa are analyzed. The authors pay attention to current legislation of BRICS countries regarding competition protection with regard to provisions related to ‘horizontal’ and ‘vertical’ restrictions of trade, concerted practices, deceptive conducts and collusions, unfair sales techniques, pricing and selling strategies. It can be argued that our society is interested in the engagement of a population in trade and industrial activity, however, this rule allows exceptions: restrictions of freedom of trade can be justified by exceptional circumstances in certain cases and under certain circumstances.